(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The increasingly complex and dynamic nature of contemporary problems demands innovative and effective problem-solving approaches. This study explores the synergistic relationship between creative and critical thinking in tackling modern-day challenges. The research investigates the hypothesis that the integration of creative and critical thinking skills enhances problem-solving efficacy. A qualitative method of research was employed to see this work to completion. The findings reveal a significant positive correlation between creative and critical thinking skills and problem-solving success. Notably, the study identifies key factors that facilitate or hinder the effective application of creative and critical thinking, including organizational culture, education, and training. This research contributes to the existing body of knowledge by providing empirical evidence of the complementary nature of creative and critical thinking in problem-solving. The study recommends that educators, policymakers, and organizational leaders prioritize the development of both creative and critical thinking skills, and foster a culture that encourages their integration. By doing so, individuals and organizations can enhance their capacity to tackle complex problems and thrive in an increasingly uncertain world.